Tutoring in the metaverse. Study on student-teachers’ and tutors’ perceptions about NPC tutor - Agrati, Laura Sara (Frontiers in Education, 2023)
The metaverse is defined as a new frontier for anyone's everyday life and a new challenge for the training and the professional development. The extended reality of the metaverse offers a new learning environment in which additional educational roles intervene to support the teaching and learning processes. The work explores some aspects of the metaverse as a support for the initial training of teachers. It presents a study on the student-teachers' and tutors' perceptions about the socalled 'non-player characters' (NPC tutor, peer and tutee) that started from the following questions: how useful are NPCs roles perceived to be? How useful is NPC tutor perceived to be in supporting the teaching and learning processes? A survey collecting quantitative and qualitative data was carried out on the perceptions that student-teachers and school tutors of a qualifying course for teaching have, specifically, of the NPC tutor and peer in the metaverse. The analysis found some differences in expectations between student-teachers and school tutors with respect to the metaverse, to the new educational roles related and, specifically, to the NPC tutor role. The triangulation of the early data is highlighting a general new look at the possibilities offered by the metaverse -in monitoring the learning program and in decision-making practices -as well as expectation about the teachers training -Artificial Intelligence relationship. The results of study regarding the perceptions of student-teachers and school tutors on the metavers and on the role of the NPC tutor are offered as insights to be explored, through further investigations, to those responsible for teacher training courses and to the research that today investigates the learning effects of the metaverse as a potential professional training environment.